Pengaruh Healthy Lifestyle, Product Quality Dan Harga Terhadap Keputusan Pembelian Susu Bubuk Frisian Flag Di Kota Semarang - Aeini Mulia Evi Diana; Imam Nuryanto (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to analyze the influence of a healthy lifestyle, product quality and price on purchasing decisions of Frisian Flag powdered milk in Semarang City. The data collection method used purposive sampling with a total sample of 112 respondents through questionnaires distributed online and offline. The data collection technique uses primary data in the form of a questionnaire and uses a Likert scale in selecting assessment responses. The analytical method used is multiple linear analysis. The results obtained show that product quality and price have a positive and significant effect on purchasing decisions, while healthy lifestyle has a positive but not significant effect on purchasing decisions.